Clinical and Genetic Spectrum of Stargardt Disease in Argentinean Patients - Mena, Marcela D.; Moresco, Angélica A.; Vidal, Sofía H.; Aguilar-Cortes, Diana; Obregon, María G.; Fandiño, Adriana C.; Sendoya, Juan M.; Llera, Andrea S.; Podhajcer, Osvaldo L. (Frontiers in Genetics, 2021)
Purpose: To describe the clinical and molecular spectrum of Stargardt disease (STGD) in a cohort of Argentinean patients Methods: This retrospective study included 132 subjects comprising 95 probands clinically diagnosed with STGD and relatives from 16 of them. Targeted next-generation sequencing of the coding and splicing regions of ABCA4 and other phenocopying genes (ELOVL4, PROM1, and CNGB3) was performed in 97 STGD patients. Results: We found two or more disease-causing variants in the ABCA4 gene in 69/95 (73%) probands, a single ABCA4 variant in 9/95 (9.5%) probands, and no ABCA4 variants in 17/95 (18%) probands. The final analysis identified 173 variants in ABCA4. Seventy-nine ABCA4 variants were unique, of which nine were novel. No significant findings were seen in the other evaluated genes. Conclusion: This study describes the phenotypic and genetic features of STGD1 in an Argentinean cohort. The mutations p.(Gly1961Glu) and p.(Arg1129Leu) were the most frequent, representing almost 20% of the mutated alleles. We also expanded the ABCA4 mutational spectrum with nine novel disease-causing variants, of which eight might be associated with South American natives.